THE INFLUENCE OF SUBJECTIVE NORMS, TAX SOCIALIZATION AND TAX ADMINISTRATION SERVICES TO MSMES INDIVIDUAL TAX COMPLIANCE WHO REGISTERED AT NORTH JAKARTA REGIONAL TAX OFFICE - Finrely, Carsen; Yuniarwati , Yuniarwati (International Journal of Application on Economics and Business, 2023)
Indonesia's tax ratio is at a lower level compared to countries that are members of the G-20 and ASEAN, the Covid-19 pandemic has leads Internal Service Revenue to make a reform from digitizing tax administration services and tax socialization. Tax incentives provided for all Indonesian people who get affected by Covid-19 is expected to increase the subjective norms of the society, especially MSME individual’s voluntary tax compliance level. This Study was conducted on individual MSME taxpayers registered at the North Jakarta IRS, and has a hypothesis that subjective norms, tax socialization and tax administration services have a positive and significant effect on the tax compliance of MSME individual taxpayers. The results of data analysis with Smart PLS 4.0, the result indicates that the hypothesis can be accepted and supported except for tax socialization.